Tick-borne encephalitis in Japan, Republic of Korea and China - Yoshii, Kentaro; Song, Joon Young; Park, Seong-Beom; Yang, Junfeng; Schmitt, Heinz-Josef (Emerging microbes & infections, 2017)
Tick-borne encephalitis virus (TBEV) causes mild or moderate febrile illness in humans that may progress to encephalitis, leading to severe long-term complications and sometimes death. TBEV is prevalent in the Eurasian continent and has been isolated in China, Japan and Republic of Korea (ROK). The TBEV isolates from Japan are of the Far-Eastern subtype; in ROK, the isolates are of the Western subtype; and all TBEV isolates in China are of the Far-Eastern subtype, except one strain that was identified most recently as the Siberian subtype. TBE is endemic to the northeast, northwest and southeast of China; only two confirmed TBE cases have been reported in Japan to date; and no TBE case has been confirmed in ROK. For TBE patients in China, the onset of disease is acute with no biphasic course for disease presentation. The clinical spectrum of disease phenotypes may be wider than currently understood, since serological evidence suggests the presence of TBEV infections in healthy people, indicating that asymptomatic or unspecific manifestations of TBEV infection may exist. The current treatment for TBE is supportive care. In China, vaccines against TBEV have been developed and are available with demonstrated immunogenicity and safety, although efficacy data are lacking. No vaccines are available in ROK or Japan.